1998
DOI: 10.1046/j.1523-1755.1998.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of the renin-angiotensin system and the outcome of focal segmental glomerulosclerosis in children

Abstract: Homozygosity for the ACE insertion allele may have a protective effect in children with FSGS and can serve as a positive prognostic indicator at diagnosis. The D allele may exert a detrimental dominant effect on outcome. Neither the ACE gene polymorphism nor the other RAS polymorphisms studied are associated with disease prevalence. The AT1R and angiotensinogen gene polymorphisms are not associated with progression of renal disease in FSGS. Ethnic differences in the clinical course of the disease are not linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 37 publications
(41 reference statements)
8
60
2
Order By: Relevance
“…Different results have been reported from the studies of ACE I/D polymorphism in children with NS and other renal diseases. 4,7,8,27,28,[35][36][37][38] In these studies, it was reported that the D polymorphism of ACE gene is a risk factor for the progression to ESRD in patients with FSGS, IgA nephropathy, hypertension and diabetic nephropathy. But it was also reported that no association was detected between the polymorphism of both AT 1 R and AGT and disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different results have been reported from the studies of ACE I/D polymorphism in children with NS and other renal diseases. 4,7,8,27,28,[35][36][37][38] In these studies, it was reported that the D polymorphism of ACE gene is a risk factor for the progression to ESRD in patients with FSGS, IgA nephropathy, hypertension and diabetic nephropathy. But it was also reported that no association was detected between the polymorphism of both AT 1 R and AGT and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…6 RAS-related studies in children have particularly focused on nephrotic syndrome (NS) patients. 7,8 The polymorphism 138 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study from Israel reported that they achieved remission in two thirds of children with the II genotype, but in only 24% of children with the DD and ID genotype. 12 They concluded that ACE genotype interfered with steroid response in the patients with FSGS. Lee and his colleagues reported in a Korean population a steroid response in 1/8 patients with the DD genotype and 5/18 patients with the other genotypes.…”
mentioning
confidence: 99%
“…It has been found that homozygosity for the ACE I allele may have a protective effect in children with FSGS and can serve as a positive prognostic indicator at diagnosis, while the D allele may exert a detrimental dominant effect on outcome. 21 Recently, it has also been shown that the DD genotype may be a risk factor for the development of progressive renal impairment in children with FSGS. 22 Another study demonstrated that ACE I/D polymorphism does not contribute to the steroid resistance, but carriers of I/D genotype introduce 2.8-fold risk for NS.…”
Section: Discussionmentioning
confidence: 99%